(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the carpet weaving of the peoples of Central Asia. An analysis of carpet weaving as one of the oldest types of decorative and applied art is carried out. The development of carpet weaving techniques of the peoples of Central Asia and the features of making carpets of various types are described.